PENGARUH REMUNERASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Muhammad Syawal; Hasanuddin Bua; Rahmat Madjid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This research aimed to find out and analyze (1) the effect of remuneration, working environment, and working discipline on the employee performance at Halu Oleo University, (2) the effect of remuneration on the employee performance, (3) the effect of working environment on the employee performance, and (4) the effect of working discipline on the employee performance.This research employed the quantitative analysis method and the data were analyzed using multiple regression analysis. The population consisted of all 484 staff at Halu Oleo University. The number of respondents was 97 persons who were selected using slovin technique.The research results showed that jointly, the remuneration, working environment, and working discipline had positive and significant effect on the employee performance at Halu Oleo University. the remuneration had positive and significant effect on the employee performance at Halu Oleo University, working environment had positive and significant effect on the employee performance at Halu Oleo University, working discipline had positive and significant effect on the employee performance at Halu Oleo University.Keywords: the remuneration, working environment, working discipline, employee performance